Antibacterial Activity of Ocimum citriodorum Leave Extracts Against Shigella dysenteriae - Oom Komala; Novi Fajar Utami; Saraswati Darmawan (Universitas Pakuan, 2023)
Dysentry is a disease caused by infection of Shigella dysenteriae (S. dysenteriae). This type of acute diarrhea characterized by the liquid stool mixed with blood and mucus caused by these bacteria. Ocimum citriodorum (O. citriodorum) leaves contain various chemical compounds that can inhibit the growth of diarrhea-causing bacteria. This study aims to determine the antibacterial activity of O. citriodorum leaves extracts obtained from graded extraction method against S. dysenteriae. The O. citriodorum leaves were extracted using ethanol, ethyl acetate, and n-hexane solvents sequentially. The Minimum Inhibitory Concentration (MIC) test was carried out using dilution method. The positive control used was 10 ppm ciprofloxacin (0.002%). The results showed that the extract of n-hexane, ethyl acetate, and ethanol of O. citriodorum leaves all three have antibacterial activity against S. dysenteriae with the same MIC value of 15%. The most effective MIC of n-hexane, ethyl acetate, and ethanol extract of O. citriodorum leaves was found at a concentration of 15% zone inhinbition with ethanol extract of O. citriodorum leaves